Synthesis, Characterization, and Photoluminescence on the Glass Doped with AgInS2 Nanocrystals - Dewu Yin; Lang Pei; Zhen Liu; Xinyu Yang; Weidong Xiang; Xiyan Zhang (Advances in Condensed Matter Physics)
We demonstrated a synthetic process on the glass doped with AgInS2 nanocrystals through sol-gel method under a controlled atmosphere. X-ray powder diffraction and X-ray photoelectron spectra revealed that the AgInS2 crystalline phase had formed in the glass matrix. Transmittance electron microscopy showed that these AgInS2 crystals had spherical shape and good dispersed form in the glass matrix, and their diameter distribution was mainly focused on three size regions. Furthermore, the glass doped with AgInS2 nanocrystals exhibited three photoluminescence peaks located at 1.83 eV, 2.02 eV, and 2.21 eV, which were ascribed to the introduction of AgInS2 nanocrystals in the glass.